Enhancing DevOps Engineering Education Through System-Based Learning Approach - Zarour Mohammad; Akour Mohammed; Alenezi Mamdouh (De Gruyter, 2024)
System-based learning (SBL) in engineering domains integrates systems thinking and engineering principles to develop a system. In software engineering, to develop software using the DevOps process, using SBL environment, students gain a comprehensive understanding of the DevOps software development process and apply theoretical concepts to real-world problems by implementing a complete system pipeline, encompassing the design, development, testing, and deployment of software systems. This article introduces an SBL approach to teaching DevOps engineering, addressing the limitations of traditional methods in equipping students with the necessary skills and knowledge. To evaluate the effectiveness of the SBL approach, a case study was conducted to teach a DevOps course within an undergraduate software engineering program. Students completed a project involving the implementation of a system pipeline from requirement gathering to deployment. Results from the case study demonstrate that the SBL approach has improved students' understanding of DevOps engineering and the software development big picture. The approach enhanced students' systems thinking and problem-solving capabilities and prepared students for the challenges of a rapidly evolving technological landscape.